Welfare and vulnerability in Tajikistan: Evidence from twelve districts in Khatlon Province, 2015 - 2023 - Lambrecht, Isabel B.; Mardonova Tolibkhonovna, Mohru; Akramov, Kamiljon T. (International Food Policy Research Institute, 2023)
In February-March 2023, 2,000 households were interviewed about their socio-economic conditions in twelve districts of Khatlon Province which constitute USAID’s Zone of Influence (ZOI). Based on these recent survey data as well as former survey data from 2015 and 2012, we present findings here related to changes in poverty over the past eight to ten years. Key findings - Housing conditions improved, indicating improved living conditions. Only 1 percent of households had improved sanitation in 2015, but nearly half (49 percent) of all households did so in 2023. - Fewer households experience hunger in 2023 than in 2015. Fewer households reported having had no food in the home at least once in the past month (40 percent in 2015 vs. 27 percent in 2023), and household hunger scores declined (from 0.667 in 2015 to 0.523 in 2023). - Expenditures on food increased, but these were used to purchase more expensive food rather than improving dietary quality. Consumption patterns mainly shifted towards more expensive sources of protein, i.e. the consumption of meat, chicken and fish. Consumption of other food groups, however, reduced. This led to a stagnation in diet diversity among women of which 30 percent have inadequate dietary diversity. Women have significantly worse dietary quality than men but household consumption patterns do show improvements over time. - Total consumption expenditures increased nearly ten percent (in real terms) between 2015 and 2023, which is also accompanied by a significant drop in poverty over that period, from 39.1 per-cent to 28.7 percent. - Movements of households in and out of poverty and fluctuations in household food security status between 2015 and 2023 suggest that a significant share of households are at risk of falling back into poverty in the face of adversity. - Correlates with consumption expenditures, poverty, and the prosperity gap demonstrate that households with more household members, with fewer livelihood sources, and in more remote locations are worse off. Households with more women are more likely to be poor given women’s limited income-generating opportunities. - Households that participated in agriculture development activities were approximately 12.7 per-cent more likely to move out of poverty than other households